2015
DOI: 10.1007/s00247-015-3493-7
|View full text |Cite
|
Sign up to set email alerts
|

Disk abnormality coexists with any degree of synovial and osseous abnormality in the temporomandibular joints of children with juvenile idiopathic arthritis

Abstract: Disk abnormalities were frequent. Disk displacement also occurred in joints with early temporomandibular joint arthritis, i.e., with normal bone shape. Other disk abnormalities were found in joints with bone abnormalities. Attention should be paid to disk abnormalities both in early and long-standing temporomandibular joint arthritis in children with juvenile idiopathic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
2
17
2
Order By: Relevance
“…We are not aware of any TMJ studies in children with JIA that have used this general definition of arthritis. In line with other studies , clinical TMJ involvement (whether active or not) in our study was based on the presence of TMJ pain and/or LOM. The observed low frequency of clinical TMJ involvement was therefore not surprising.…”
Section: Discussionsupporting
confidence: 83%
“…We are not aware of any TMJ studies in children with JIA that have used this general definition of arthritis. In line with other studies , clinical TMJ involvement (whether active or not) in our study was based on the presence of TMJ pain and/or LOM. The observed low frequency of clinical TMJ involvement was therefore not surprising.…”
Section: Discussionsupporting
confidence: 83%
“…In a recent MRI study, no TMJs in children with JIA had effusion without synovial thickening. 18 The ultrasonography image is limited to the lateral part of the joint, and a joint with focal medial synovitis may have a normal capsular width. A laterally or medially displaced disc may result in an altered capsular width at the condylar level.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that 78% of children with JIA and TMJ symptoms had evidence of synovitis on MRI. 18 MRI should be performed prior to injection therapy of the TMJ, since there are obvious pitfalls with the ultrasonography examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations